Management of obstructive sleep apnoea syndrome. Issue 8 (12th September 2016) - Ratnakumar, Prashanthi; Manuel, Ari
Abstract : Obstructive sleep apnoea (OSA) describes the pathological narrowing and collapse of the upper airway in recurrent episodes during sleep. This can result in a variety of symptoms that markedly affect quality of life. In addition, other chronic complications, most significantly the development of long‐term cardiovascular disease, are increasingly becoming recognised.